Transcriptomics reveal useful resources for examining fruit development and variation in fruit size in Coccinia grandis - Panda, Mitrabinda; Pradhan, Seema; Mukherjee, Pulok K. (Frontiers in Plant Science, 2024)
The Cucurbitaceae family comprises many agronomically important members that bear nutritious fruits and vegetables of great economic importance. Coccinia grandis, commonly known as Ivy gourd, belongs to the Cucurbitaceae family and is commonly consumed as a vegetable. We performed comparative transcriptomics of two Ivy gourd cultivars namely "Arka Neelachal Kunkhi" (larger fruit size) and "Arka Neelachal Sabuja" (smaller fruit size) differing in their average fruit size. We performed de novo transcriptome assembly of two varieties of ivy gourd ("Arka Neelachal Kunkhi" and "Arka Neelachal Sabuja") by taking fruits at different stages of development (5, 10, 15, and 20 days after anthesis DAA). We assembled the data from RNA-seq of the fruits and leaves to obtain 155205 unigenes having an average contig size of 1472 bp. Unigenes were annotated on different publicly available databases (Uniref90, Uniprot-SwissProt, KEGG, KOG, Pfam) to categorize them into different biological functions. Out of these, 7635 unigenes were classified into 38 transcription factor (TF) families, of which Trihelix TFs were most abundant. We found a total of 11,165 unigenes to be differentially expressed in both the varieties of ivy gourd and the in silico expression results were validated through real-time PCR. We also identified 98768 simple sequence repeats (SSRs) in the transcriptome of Ivy gourd and the information obtained can be helpful in selecting candidate genes that can be implicated for regulating fruit development and size in other fruit crops.